White light generation and amplification using a soliton pulse within a nano-waveguide - Khuntong Sarapat; Jalil Ali; Preecha P. Yupapin; Artit Worrarutkul; Wanchai Khunnam (My University, 2009)
We propose a novel system of a nano-waveguide that can be used to generate the continuous optical spectrum, i.e. white light. A system consists of two micro and a nano ring resonators that can be integrated into a single system. The large bandwidth signa is generated by using a soliton pulse propagating within a Kerr type nonlinear medium, whereas the continuous bandwidth or wavelength of light signal can be performed. Results obtained have shown the potential of using such system for white light source generation and amplification, which is discussed. The amplified pulse can be stored within a nano-waveguide, which is allowed to form the continuous spectrum after amplification. Alternatively, the low level solar radiation can be amplified, and the bandwidth signals can also be enlarge.
Keywords: Waveguide; Photonic and Optical Devices